Essentials of English grammar : English plus - Alcantara, Rebecca D.; Cabanilla, Josefina Q. (Quezon City, Philippines : Katha Publishing Co, Inc., 1999)
Essentials of English Grammar brings the insights of modern grammarians to the perennial concerns of the English classroom. The major concern in this book is with the grammar of English.
Unit I. Parts of Speech -- Unit II. The Verbals -- Unit III. Word Groups -- Unit IV. The Sentence -- Unit V. Grammatical Conventions -- Bibliography.
Includes bibliographical references.
Keywords: ENGLISH USAGE -- GRAMMAR -- ENGLISH LANGUAGE